Lake water chemistry profiles - Diefendorf, Aaron F; Dietrich, Watts; Naake, Hans H; Lowell, Thomas V; Corcoran, Megan C (In: Diefendorf, AF et al. (2025): Diatom-derived highly branched isoprenoids in lake waters and sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979496, 2025)
Diatom-derived highly branched isoprenoids (HBIs) are found extensively in marine sediments, but are observed in a limited number of lake sediments. To expand on this record, between 2022 and 2024, we collected lake surface sediment samples from 50 lakes in the United States of America from the Midwest and Northeast. Studied lakes capture a range in climate, water chemistry (e.g., pH, salinity, alkalinity), size, and trophic states. Lakes also vary in their diatom species compositions. Water chemistry profiles were measured in each lake. Water chemistry parameters included pH, conductivity, salinity, oxidation reduction potential, dissolved oxygen and were measured using a multiparameter sonde.
Keywords: Biomarkers; carbon isotope composition of DIC; Carbon isotopes; diatoms; highly branched isoprenoid (HBI); Highly branched isoprenoid (HBI) biomarkers; lakes; Lake sediment; Organic Geochemistry